Prioritizing Governance of the COBIT 2019 DSS02 Domain Based on Incident Management Data - Lahan Adi Purwanto; Achmad Fauzan (Politeknik Ganesha Medan, 2026)
Information technology (IT) governance plays a crucial role in ensuring service quality, and COBIT 2019 provides a structured framework for incident management through the DSS02 domain. However, DSS02 implementation is commonly evaluated using surveys or capability assessments that are subjective, difficult to reproduce, and challenging to verify independently, despite the availability of detailed operational event logs in IT service management platforms. This study proposes an event-log-based approach to identify governance improvement priorities within the COBIT 2019 DSS02 domain. Five operational indicators were developed, namely the Process Complexity Index (PCI), Operational Interaction Index (OII), Reassignment Indicator (RI), Reopened Incident Indicator (RII), and Delay Severity Index (DSI). These indicators were mapped to DSS02 subprocesses and integrated into a Governance Priority Score (GPS), which was evaluated using local sensitivity analysis and Spearman correlation analysis on a ServiceNow event log containing 141,707 events and 24,918 incidents. The results identified DSS02.04 (Investigate, Diagnose and Resolve) as the highest governance priority (GPS = 5.06), followed by DSS02.02 (4.27) and DSS02.03 (1.14). Sensitivity analysis showed that moderate (±10%) changes in indicator weights did not alter the priority ranking, while correlation analysis revealed a strong relationship between reassignment frequency and incident modification activity (ρ = 0.67). The proposed approach provides an objective, reproducible, and auditable data-driven prioritization mechanism that complements conventional survey-based governance assessment using operational event logs.